Oil and property rights. (December 2022) - de Soysa, Indra; Krieger, Tim; Meierrieks, Daniel
Abstract: We investigate the role of oil in economic institutions for a sample of 150 countries between 1960 and 2014. We find that higher per capita values of oil production result in weaker economic institutions in the form of lower levels of private property rights protection. This result is robust to alternative instrumental-variable approaches as well as different operationalizations of oil income and production as well as economic institutions. We argue that our finding is indicative of oil interest groups using their economic power to achieve weaker property rights to maintain their economic-political position in society. We also provide evidence that oil induces clientelism, corruption and the repression of dissenting political voices. We argue that this finding is consistent with the idea that oil interest groups translate their outsized economic into political power through these transmission channels to achieve lower levels of property rights protection. Highlights: Oil-rich countries exhibit weak institutions and little diversification. Weak institutions are thought to be related to a natural resource curse. We argue that interest groups with access to natural resource wealth use their economic powerto block competition . We find support for our propositions that oil weakens property rights. Our results are robust to rigorous testing in an instrumental variables framework. Our empirical results are consistent with interest groups using their economic power to constrain property rights, which benefits incumbents